Ecdysone receptor knockdown: implications on longevity, reproductive success and plasmodium susceptibility in the malaria vector anopheles funestus - Maharaj, Surina (My University, 2021)
Malaria is a devastating disease in humans, transmitted by female Anopheles mosquitoes infected with Plasmodium parasites. Current insecticide-based strategies exist to control the spread of malaria by targeting vectors. Unfortunately, the effectiveness of these vector control methods is declining due to increasing insecticide resistance in vector populations. It is therefore essential to develop novel vector control methods that can efficiently target transmission reducing factors such as vector density (influenced by vector survival and reproduction) and competence (influenced by transmission ability). A possible vector control candidate gene, the ecdysone receptor (EcR) regulates longevity, reproduction, immunity, as well as many other physiological processes in several insects and malaria vectors. The malaria vector, Anopheles funestus (An. funestus) is responsible for the majority of malaria outbreaks in South Africa, however, the function of EcR in this vector has not previously been studied. This study therefore aimed to determine the extent of EcR regulation on longevity, reproduction and susceptibility to Plasmodium falciparum (P. falciparum) in An. funestus. In this study, RNA interference was used to reduce EcR expression levels in An. funestus females and investigate how it impacted their longevity, reproduction and susceptibility to P. falciparum infection. Additionally, the expression levels of EcR, and reproduction genes lipophorin (Lp) and vitellogenin receptor (VgR) as well as the immune gene, leucine rich immune molecule 9 (LRIM9) were determined using qPCR and relative expression analysis was performed. EcR depleted mosquitoes had a shorter lifespan, were less fecund, less fertile, and had reduced P. falciparum infection intensity. Moreover, gene expression analyses revealed that mosquitoes with reduced EcR expression also had depleted Lp, VgR and LRIM9 expression levels. As EcR regulates processes affecting vector density and competence, this study provides the first experimental evidence that supports EcR as a novel target in the development of vector control measures targeting An. funestus.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2021